PELATIHAN TEKNIK PARAFRASE UNTUK MENINGKATKAN KUALITAS PENULISAN ILMIAH MAHASISWA STKIP MELAWI - Mastiah, Mastiah; Tirsa, Aprima (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract:This community service program was conducted as an effort to address the low proficiency of students in producing accurate and effective paraphrases. The primary target of this training was final-year students working on their theses or dissertations, as well as students enrolled in research methodology courses. The training was implemented through three main stages: preparation, execution, and evaluation. The results indicate that the training successfully enhanced students' paraphrasing skills. Most participants demonstrated improved application of paraphrasing techniques and a deeper understanding of the importance of academic integrity.Keyword: Paraphrasing, Academic Proficiency, Academic Integrity, Training Abstrak: Kegiatan pengabdian ini diselenggarakan sebagai upaya untuk mengatasi rendahnya kemampuan mahasiswa dalam melakukan parafrase yang baik dan benar. Target utama pelatihan ini adalah mahasiswa tingkat akhir yang sedang menulis tugas akhir atau skripsi, serta mahasiswa yang mengikuti mata kuliah metodologi penelitian. Pelatihan dilaksanakan melalui tiga tahapan utama: persiapan, pelaksanaan, dan evaluasi. Pelatihan ini berhasil meningkatkan kemampuan parafrase mahasiswa. Sebagian besar mahasiswa berhasil mengaplikasikan teknik parafrase dengan lebih baik dan memahami pentingnya kejujuran akademik.Kata kunci: Parafrase, Kemampuan Akademik, Kejujuran Akademik, Pelatiha